The Antarctic ozone minimum - Relationship to odd nitrogen, odd chlorine, the final warming, and the 11-year solar cycle - Callis, L. B.; Natarajan, M. (1986)
Photochemical calculations along 'diabatic trajectories' in the meridional phase are used to search for the cause of the dramatic springtime minimum in Antarctic column ozone. The results indicate that the minimum is principally due to catalytic destruction of ozone by high levels of total odd nitrogen. Calculations suggest that these levels of odd nitrogen are transported within the polar vortex and during the polar night from the middle to upper stratosphere and lower mesosphere to the lower stratosphere. The possibility that these levels are related to the 11-year solar cycle and are increased by enhanced formation in the thermosphere and mesosphere during solar maximum conditions is discussed.